Licaria leonis (Lauraceae), una nueva especie del Pacífico costarricense, y algunas notas sobre Licaria multinervis H. Kurz - Gómez-Laurito, Jorge; Estrada, Armando (Lankesteriana: International Journal on Orchidology, 2016)
A new species of Licaria Aublet (Lauraceae) from the midlands of the Pacific slope of Costa Rica is described and illustrated here. This new species is compared with L. multinervis and an undescribed species of Endlicheria Nees is mentioned only as a possible immature form of L. multinervis.